2015
DOI: 10.1007/s00170-015-7124-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of thrust forces and delamination in drilling carbon-reinforced plastics (CFRPs) using a tapered drill-reamer

Abstract: The thrust forces and delamination in drilling carbon-reinforced plastics (CFRPs) using a tapered drillreamer have been studied by experimental and theoretical analyses. A theoretical drilling model of the tapered drillreamer has been established to study the developing process of the push-out delamination, and a comprehensive analysis for the thrust force and the delamination has been developed in the present study. The results obtained in this study show that the maximum thrust force measured in the drilling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Abrão et al [57] showed that 56% of the tools used for drilling polymer composites have a special geometry. Some of the special drilling tools developed for CFRP cutting are as follows: (i) double point angle twist drills [58][59][60][61][62][63][64], (ii) brad and spur drills [21,[65][66][67][68][69][70], (iii) dagger drills (one-shot drills) [28,31,[67][68][69][70][71][72][73], (iv) step drills [67,68,[74][75][76][77][78][79][80], (v) core drills [81,82] and (vi) special core drills [83][84][85]. These special drilling tools are reviewed and discussed in detail by Geier et al [55].…”
Section: Conventional Drilling and Helical Milling Of Cfrpsmentioning
confidence: 99%
“…Abrão et al [57] showed that 56% of the tools used for drilling polymer composites have a special geometry. Some of the special drilling tools developed for CFRP cutting are as follows: (i) double point angle twist drills [58][59][60][61][62][63][64], (ii) brad and spur drills [21,[65][66][67][68][69][70], (iii) dagger drills (one-shot drills) [28,31,[67][68][69][70][71][72][73], (iv) step drills [67,68,[74][75][76][77][78][79][80], (v) core drills [81,82] and (vi) special core drills [83][84][85]. These special drilling tools are reviewed and discussed in detail by Geier et al [55].…”
Section: Conventional Drilling and Helical Milling Of Cfrpsmentioning
confidence: 99%
“…In FRP/metal stack arrangement application, metal stack such as aluminum or titanium stack acts as a backup support plate to prevent delamination and bending deformation commonly. Many researchers reported about backup support and two-sided support with and without pre-drilled plates/fixtures 9,10,18,21,33,36,40,42,45,46 as a basic methodology to prevent delamination and bending of multimaterial during their studies of drilling of laminate composite material with other various methodologies and strategies of drilling.…”
Section: Effect Of Backup Supportmentioning
confidence: 99%
“…To address the drilling issues of CFRPs, a large amount of research work has been carried out worldwide by scholars [10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], covering a variety of aspects involving drilling forces, drilling-induced damages, tool wear, etc. Some drilling-induced damage, including delamination, hole dimensional inaccuracy, surface roughness, fiber pullouts, and uncut fibers, have been investigated in the scientific literature [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the fiber cutting modes changed dynamically with the composite sequence, and the local feed forces generated on the hole bottom could be correlated with the delaminating aspects. Su et al [28] addressed the thrust forces and delamination issues when drilling CFRPs using a tapered drill-reamer and found that the drilling parameters significantly affected the maximum thrust force measured in the drilling stage instead of the reaming stage. Ameur et al [29] conducted drilling studies on CFRP materials using different types of tool materials.…”
Section: Introductionmentioning
confidence: 99%